In the Garden of Anthropos - Katerina Labrou; Christos Montsenigos (Footprint)
The term ‘planetary garden’ was coined by Gilles Clement to refer to the privileged site of the planetary mixing of species that is managed by humans. In the face of the ongoing environmental collapse, we envision the garden as a new locus for symbiotic attachment and original exchange between human and non-human ecologies. Drawing on the garden metaphor, we discuss the conceptual and ecological impacts of human stewardship of the environment. Recognising ecosystems as changing fields of social and technical interactions, we evaluate how conservation strategies shift in tandem with these changes. We explore the influence of emerging technologies on human understanding of natural ecosystems and on societal approaches to conservation. Envisioning the future, we are mapping out the need for human-centric technologies to foster new forms of agency between humans and their environments. While any technological promise does not come without ethical and technical challenges, we advocate for ecological intelligence (EI), a spatialised human-AI collaboration scheme, as a critical condition for reimagining and upscaling conservation practices in the Anthropocene.